Consumer Preferences for Verified Pork-Rearing Practices in the Production of Ham Products - Melissa G.S. McKendree; Widmar Nicole Olynk; David L. Ortega; Kenneth A. Foster (Journal of Agricultural and Resource Economics, 2013)
A hypothetical choice experiment was conducted to determine consumers' willingness to pay for three verified production practice attributes (pasture access, antibiotic use, and individual crates/stalls) in smoked ham and ham lunchmeat. These attributes were verified by the USDA Process Verified Program (PVP), a retailer, or the pork industry. Willingness to pay for verified attributes varied across attributes and verifying entity for both products. Consumers were willing to pay the most for attributes verified by the USDA-PVP. No statistical differences, relative to the product price level, were found across products for the same attribute-verifier combination.